2007
DOI: 10.1186/1471-2199-8-113
|View full text |Cite
|
Sign up to set email alerts
|

Relative quantification of mRNA: comparison of methods currently used for real-time PCR data analysis

Abstract: BackgroundFluorescent data obtained from real-time PCR must be processed by some method of data analysis to obtain the relative quantity of target mRNA. The method chosen for data analysis can strongly influence results of the quantification.ResultsTo compare the performance of six techniques which are currently used for analysing fluorescent data in real-time PCR relative quantification, we quantified four cytokine transcripts (IL-1β, IL-6 TNF-α, and GM-CSF) in an in vivo model of colonic inflammation. Accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(135 citation statements)
references
References 23 publications
(33 reference statements)
1
134
0
Order By: Relevance
“…Using the LinRegPCR method to calculate E fi , Č ikos et al (9) found that the interleukin 6 gene amplified with an E fi of 1.88, while the beta actin gene amplified with an E fi of 1.99. Moreover, they found that these differences between the genes remained regardless of the method used to determine E fi (9). Similarly, other studies found that E determined for the same PCR template is more constant (5, 9, 26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the LinRegPCR method to calculate E fi , Č ikos et al (9) found that the interleukin 6 gene amplified with an E fi of 1.88, while the beta actin gene amplified with an E fi of 1.99. Moreover, they found that these differences between the genes remained regardless of the method used to determine E fi (9). Similarly, other studies found that E determined for the same PCR template is more constant (5, 9, 26).…”
Section: Resultsmentioning
confidence: 99%
“…We calculated E sample and E standard as the mean E fi from individual replicates, because previous studies recommended using the means of E fi (9,30,40). Alternatively, E sample and E standard could be estimated from dilution series, E ds (equation 3) (31).…”
Section: Bacterial Cultures (I)mentioning
confidence: 99%
“…PCR efficiency was determined for each gene by LinRegPCR program (Ramakers et al, 2003;Ruijter et al, 2009). This software was successfully used previously to calculate PCR efficiency (Č ikoš et al, 2007;Feng et al, 2008;Regier & Frey, 2010;Aglawe et al, 2012, Borges et al, 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Primers and their PCR product sizes are shown in Table 5. For quantification, we used the relative standard curve method (Cikos et al 2007). Ribosomal protein L13a (Rpl13a) was used as a reference gene.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%